Cognitive and neuropsychiatric outcomes in economically active young patients with epilepsy: a case-control study from a secondary medical center in Mexico - Rodolfo Manuel Román-Guzmán; Raúl Medina-Rioja; Ildefonso Rodríguez-Leyva; Cristina Monzón-Tapia; Luis Mario Méndez-Casillas; José Luis Rodríguez-Castro; Luis Daniel Marquez-Farias; David Martínez-González; Hector G. Hernández-Rodríguez; Denisse Grace Martínez-Roque; Mario Ohtlitonali Hernández-Bautista; Sahian Flores-Guerrero; et al. (Exploration of Neuroprotective Therapy)
Aim: Epilepsy is associated with cognitive and neuropsychiatric impairments, affecting attention, memory, executive functions, and emotional well-being. While these impairments are well-documented in general epilepsy populations, limited research focuses on economically active young adults who face unique cognitive demands in competitive academic and professional environments. The objective of this research was to evaluate the cognitive and neuropsychiatric outcomes in economically active young adults with epilepsy compared to matched controls. Methods: An observational, analytical, case-control study was conducted at a secondary medical center in Mexico. Participants included 25 patients with well-controlled epilepsy and 25 matched controls. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA) and Addenbrooke’s Cognitive Examination III (ACE-III). Anxiety and depression were evaluated using the Beck Anxiety Inventory and Patient Health Questionnaire-9 (PHQ-9). Statistical analysis included Student’s T-test and Chi-square for cognitive scores and Wilcoxon rank-sum tests for non-parametric data. Results: Cognitive impairments were significantly more frequent in patients with epilepsy than in controls, particularly in attention (p = 0.041), episodic memory (p = 0.048), clock drawing (p = 0.004), and cube copying (p < 0.001). Verbal (p = 0.011) and semantic fluency (p = 0.027) were also affected. No significant differences were observed in anxiety (p = 0.221) or depression (p = 0.800) between groups. Conclusions: Economically active young adults with well-controlled epilepsy showed significant cognitive impairments, particularly in attention, memory, visuospatial, and executive functions, independent of anxiety and depression levels. This study underscores the need for comprehensive cognitive and neuropsychiatric evaluations in epilepsy treatment, regardless of seizure control. It advocates for targeted cognitive rehabilitation and a holistic approach to epilepsy care beyond seizure frequency control.